2013
DOI: 10.2967/jnumed.112.113472
|View full text |Cite
|
Sign up to set email alerts
|

18F-FES and 18F-FDG PET for Differential Diagnosis and Quantitative Evaluation of Mesenchymal Uterine Tumors: Correlation with Immunohistochemical Analysis

Abstract: The aim of this study was to investigate the relationship between the tumor uptake of 16a-18 F-fluoro-17b-estradiol ( 18 F-FES) and 18 F-FDG using PET and expressions of sex hormone receptors, such as estrogen receptor (ER), as well as glucose transporter 1 (GLUT-1) and Ki-67 analyzed by the immunohistochemistry method in mesenchymal uterine tumors. Methods: Forty-seven patients with mesenchymal uterine tumors were studied with 18 F-FES and 18 F-FDG PET. Postoperative pathologic diagnosis revealed 33 uterine l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 26 publications
2
52
0
1
Order By: Relevance
“…The ER-specific tracer 18 F-FES has been used to characterize breast and uterine tumours with high sensitivity for noninvasive reporting of ER status [35,36,108]. Tsujikawa et al showed that 18 F-FES uptake in breast cancer patients is positively correlated with expression of ERα while 18 F-FDG uptake as expected failed to correlate with immunohistochemical scoring [35].…”
Section: Imaging Proliferation Growth and Replicative Immortalitymentioning
confidence: 96%
“…The ER-specific tracer 18 F-FES has been used to characterize breast and uterine tumours with high sensitivity for noninvasive reporting of ER status [35,36,108]. Tsujikawa et al showed that 18 F-FES uptake in breast cancer patients is positively correlated with expression of ERα while 18 F-FDG uptake as expected failed to correlate with immunohistochemical scoring [35].…”
Section: Imaging Proliferation Growth and Replicative Immortalitymentioning
confidence: 96%
“…In turn, highgrade carcinomas displayed higher 18 F-FDG-to-18 F-FES uptake ratios than did low-grade endometrial carcinomas. 18 F-FES PET also has potential to differentiate benign uterine leiomyomas from malignant uterine sarcomas on the basis of 18 F-FES uptake and 18 F-FDG-to-18 F-FES uptake ratio (47,48). Differentiation of sarcoma from leiomyoma can often be difficult with MRI (49), and 18 F-FDG PET findings can be equivocal (50).…”
Section: Non-breast Cancer Uses Of 18 F-fes Uterine Endometrium and Mmentioning
confidence: 99%
“…Differentiation of sarcoma from leiomyoma can often be difficult with MRI (49), and 18 F-FDG PET findings can be equivocal (50). Similar to endometrial pathologies, lower 18 F-FES uptake and a higher 18 F-FDG-to-18 F-FES uptake ratio have been associated with malignant sarcomas (47,48). Given the substantial management and prognostic differences between the two entities, 18 F-FES PET can potentially play a role in risk stratification of indeterminate uterine masses.…”
Section: Non-breast Cancer Uses Of 18 F-fes Uterine Endometrium and Mmentioning
confidence: 99%
“…117,118 F-FES could provide better diagnostic value for differentiating between benign leiomyoma and uterine sarcoma. 123 In terms of the prognostic role of 18 F-FDG PET/CT, limited information is available. 124 Uterine sarcoma tends to have a huge solid structure with internal heterogeneity, and parameters to evaluate the entire tumor such as MTV or TLG might be more useful than local parameters such as SUVmax.…”
Section: Uterine Sarcomamentioning
confidence: 99%